The Healthcare Conflict Scale: development, validation and reliability testing of a tool for use across clinical settings. Issue 6 (2nd November 2019) - Forbat, Liz; Mnatzaganian, George; Barclay, Sarah
ABSTRACT: Despite the widespread incidence of conflict and its detrimental impact across a range of health-care settings, there is no validated tool with which to measure it. This paper describes the international innovation of a tool to measure staff-family conflict in pediatrics, intensive care, emergency, palliative care, and nursing homes. Sixty-two health-care workers contributed to focus group discussions to refine a draft tool developed from the literature. Subsequently, 101 health-care workers applied the tool to fictionalized vignettes. The psychometric properties (construct validity, internal consistency, repeatability, and reliability) were explored using principal component analysis, Cronbach's alpha, and intra-class correlation (ICC) tests. The initial 17-item tool was reduced to seven items within three factors that explained 70.2% of the total variance in overarching construct. The internal consistency of the final overall scale was good (Cronbach's alpha: 0.750); test–retest reliability of each item was excellent with ICCs ≥0.9. This new tool can be used to identify and score conflict, making it a key reference point in healthcare conflict work across clinical specialties. It's development and testing across specialities and across countries means it can be used in a variety of contexts. The tool provides health-care professionals with a new way to identify and measure conflict, and consequently has the potential to transform health-care relationships across disciplines and settings.